2020
DOI: 10.1253/circj.cj-20-0332
|View full text |Cite
|
Sign up to set email alerts
|

Doppler-Derived Intrarenal Venous Flow Mirrors Right-Sided Heart Hemodynamics in Patients With Cardiovascular Disease

Abstract: Background: Interruption in Doppler intrarenal venous flow (IRVF) has been used in assessing renal congestion and in the prediction of prognosis of cardiovascular diseases. However, there is a paucity of pathophysiological knowledge, so we aimed to clarify the determinants of IRVF interruption. Methods and Results:Intrarenal Doppler studies were performed within 24 h before right-side catheterization studies. The interruption in IRVF in 73 patients was divided into a continuous pattern, and 4 discontinuous typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…20,21,32 From these reports, in this study, we divided the HV waveforms into 3 categories according to the position of the V wave above or below the baseline as a new classification. Similar to previous reports regarding renal congestion, [24][25][26] Doppler HV waveforms in this study were found to be associated with CVP. However, measurement of HV waveforms seemed to be superior to those of intrarenal venous flow pattern, in terms of ease of measurement and accuracy of CVP, because of their closer anatomic proximity to the heart.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…20,21,32 From these reports, in this study, we divided the HV waveforms into 3 categories according to the position of the V wave above or below the baseline as a new classification. Similar to previous reports regarding renal congestion, [24][25][26] Doppler HV waveforms in this study were found to be associated with CVP. However, measurement of HV waveforms seemed to be superior to those of intrarenal venous flow pattern, in terms of ease of measurement and accuracy of CVP, because of their closer anatomic proximity to the heart.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with atrial fibrillation, the C wave was used instead of the A wave. 20,25 Based on previous studies, [20][21][22][23] we focused on the shapes and positions of the V wave. We classified HV waveforms in accordance with the shape and position of the V wave into 3 patterns (Fig 2 ) and divided the total 350 HF patients into 3 groups: those in whom the continuous flow pattern or V wave was ambiguous (C group), those in whom the V wave ran under the baseline (U group), and those who had a reversed V wave (R group).…”
Section: Abdominal Ultrasonography and Hv Waveformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seo et al showed that IRD flow patterns correlated with right atrial hemodynamics among 73 patients who underwent right heart catheterization. 20 Right ventricular dysfunction, atrial fibrillation and TR were important determinates of the RA pressure waveforms as well as the IRD flow patterns. The IRD flow patterns were sensitive to changes in specific RA pressure waveforms rather than the mean right atrial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…But the HF patients with discontinuous pattern of IRVF had a poorer prognosis, with survival at 12 months less than 40% [ 33 ]. IRVF pattern represents a prognosis predictor in HF patients; it was correlated with the serum natremia ( p < 0.05) and logBNP ( p = 0.009) [ 34 ]. Puzzovivo et al demonstrated that the discontinuous pattern of IRVF has a negative prognostic in HF patients ( p < 0.001) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%